2019
DOI: 10.2147/copd.s187345
|View full text |Cite
|
Sign up to set email alerts
|

The association between recent hospitalized COPD exacerbations and adverse outcomes after percutaneous coronary intervention: a nationwide cohort study

Abstract: PurposeCOPD is associated with coronary artery disease, and exacerbations are major events in COPD. However, the impact of recent hospitalized exacerbations on outcomes of percutaneous coronary intervention (PCI) remains underdetermined.Patients and methodsUsing the National Health Insurance Research Database of Taiwan, we identified 215,275 adult patients who underwent first-time PCI between 2000 and 2012. Among these patients, 15,485 patients had COPD. The risks of hospital mortality, overall mortality, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 37 publications
1
14
0
1
Order By: Relevance
“…In our study, we found that the risk of MACE in T2D-THEMIS-like patients according to the multivariate model was associated with the extent and severity of atherothrombosis (MVD) and with other risk factors such as history of heart valve disease and respiratory disorders (COPD/asthma). These risk factors have previously been shown to affect outcomes in general population and diabetic patients at high risk for ischemic events, specifically in patients with T2D and CAD with no history of MI or stroke and previous PCI revascularization [40][41][42][43]. Finally, the multivariate approach also revealed that such treatments as clopidogrel and statins were associated to a lower risk for MACE after adjusting for other factors in this clinical population; further research is warranted to confirm these findings in future studies.…”
Section: Plos Onementioning
confidence: 58%
“…In our study, we found that the risk of MACE in T2D-THEMIS-like patients according to the multivariate model was associated with the extent and severity of atherothrombosis (MVD) and with other risk factors such as history of heart valve disease and respiratory disorders (COPD/asthma). These risk factors have previously been shown to affect outcomes in general population and diabetic patients at high risk for ischemic events, specifically in patients with T2D and CAD with no history of MI or stroke and previous PCI revascularization [40][41][42][43]. Finally, the multivariate approach also revealed that such treatments as clopidogrel and statins were associated to a lower risk for MACE after adjusting for other factors in this clinical population; further research is warranted to confirm these findings in future studies.…”
Section: Plos Onementioning
confidence: 58%
“…7,28 COPD is associated with cardiovascular mortality following coronary revascularization with PCI, 29 and hospitalization for AE plays a role. 30 In addition to the observational study in England and Wales 17 and post hoc cohort analysis of the SUMMIT trial, 18 several other time-based reports have shown the association between recent AE and cardiovascular events during the period following an AE. 13,14,[16][17][18]26,28 In a secondary analysis of the Understanding Potential Long-Term Impacts on Function With Tiotropium (UPLIFT) trial, AE was associated with an increased risk of severe adverse cardiovascular events within both the first 30 and 180 days following an AE episode, with the highest risk occurring in the first 30 days.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that COPD alone is an independent predictor of hospital mortality in patients after CABG [24][25][26][27][28][29]. Huang et al showed that this group of patients had an increased perioperative risk and mortality, regardless of the performed coronary intervention of percutaneous coronary intervention (PCI) or CABG [24].…”
Section: Discussionmentioning
confidence: 99%